Retrocaval ureter: the importance of intravenous urography - Hassan, Radhiana; Abd. Aziz, Azian; Che Mohamed, Siti Kamariah (Universiti Sains Malaysia, 2011)
Retrocaval ureter is a rare cause of hydronephrosis. Its rarity and non-specific presentation pose a challenge to surgeons and radiologists in making the correct diagnosis. Differentiation from other causes of urinary tract obstruction, especially the more common urolithiasis, is important for successful surgical management. Current practice has seen multislice computed tomography (MSCT) rapidly replaces intravenous urography (IVU) in the assessment of patients with hydronephrosis due to suspected urolithiasis, especially ureterolithiasis. However, MSCT, without adequate opacification ofthe entire ureter,may allow the physician to overlook a retrocaval ureter as the cause of hydronephrosis. High-resolution IVU images can demonstrate the typical appearance that leads to the accurate diagnosis of a retrocaval ureter. We reported a case that illustrates this scenario and highlights the importance of IVU in the assessment of a complex congenital disorder involving the urinary tract.